THE FORMATION AND DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS OF SECONDARY SCHOOLS (AN EXAMPLE OF CHEMISTRY) - Grabovyy, Andrii K. (Educological discourse, 2014)
The study examined the theoretical and methodological bases of formation and development of technical creativity of chemistry students of secondary schools. Methods of forming technical creativity of students in chemistry is based on the principle of unity of time limit and extracurricular acties of technical students. Pointed out in stoges in the formation of technical creativity: the initial formation of technical skills, improvement and their application. Didactic conditions effective formation of technical creativity are: creating a high level of motivation and reflection; dominance productive methods of teaching chemistry; organization of active cooperation between teachers and students in the classroom and extracurriculal classes.